Analisis Peran Bermain dalam Perkembangan Kognitif Anak Usia Dini : Suatu Pendekatan Multi Perspektif - Eka Yuliana; Ilfan Tufail (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2025)
This study aims to examine the role of play in supporting cognitive, language, and mathematical development in early childhood. Play, often considered a recreational activity, has a significant impact on developing various essential skills in children. This research uses a qualitative approach with a literature review, analyzing various sources regarding the effects of different types of play, such as role play, constructive play, and social cognitive play, on children's development. The main findings show that role play enhances language competence, while constructive play and social cognitive play contribute to the development of children's mathematical and logical skills. This study emphasizes that various types of play can enrich children's learning experiences, supporting their cognitive and social development. The results of this study affirm that play is crucial for the cognitive, language, and mathematical development of young children. Various types of play, such as constructive (puzzle building), social cognitive (cooperation), and role play (pretend play), significantly support children's thinking, learning, motor, social, and language skills.